2021
DOI: 10.3390/ijms22042194
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Hydrogen Sulfide Donors in Treating Cardiovascular Diseases

Abstract: Hydrogen sulfide (H2S) has long been considered as a toxic gas, but as research progressed, the idea has been updated and it has now been shown to have potent protective effects at reasonable concentrations. H2S is an endogenous gas signaling molecule in mammals and is produced by specific enzymes in different cell types. An increasing number of studies indicate that H2S plays an important role in cardiovascular homeostasis, and in most cases, H2S has been reported to be downregulated in cardiovascular disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 225 publications
0
16
0
Order By: Relevance
“…In particular, CSE and 3MST have been reported to be expressed in the vasculature and hence play a role in the regulation of smooth muscle vasomotor tone. CBS expression has been shown to be inversely correlated with homocysteine levels, which is a factor in the progression of CVD [21]. There are a number of reviews on H 2 S and its protective effects in the cardiovascular system [17,[19][20][21][22][23][24][25][26][27][28][29].…”
Section: H 2 S Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, CSE and 3MST have been reported to be expressed in the vasculature and hence play a role in the regulation of smooth muscle vasomotor tone. CBS expression has been shown to be inversely correlated with homocysteine levels, which is a factor in the progression of CVD [21]. There are a number of reviews on H 2 S and its protective effects in the cardiovascular system [17,[19][20][21][22][23][24][25][26][27][28][29].…”
Section: H 2 S Systemmentioning
confidence: 99%
“…CBS expression has been shown to be inversely correlated with homocysteine levels, which is a factor in the progression of CVD [21]. There are a number of reviews on H 2 S and its protective effects in the cardiovascular system [17,[19][20][21][22][23][24][25][26][27][28][29]. The expression of H 2 Sproducing enzymes has been identified in the cardiovascular system, specifically in the following cell types: smooth muscle cells, cardiomyocytes, endothelial cells and immune cells [9,10,12,19,30,31].…”
Section: H 2 S Systemmentioning
confidence: 99%
“…Zhang et al demonstrated that exogenous H 2 S protected rat cardiomyoblasts against peroxide-induced apoptosis [ 49 ], while others have shown that H 2 S has vasodilatory [ 50 ], antioxidant [ 51 ], and anti-inflammatory [ 52 ] effects in cardiac tissue. Unfortunately, the flammability and toxicity of gaseous H 2 S, not to mention its foul odor, somewhat limits its use as a therapeutic agent, while inorganic H 2 S donors such as NaHS and Na2S are limited by rapid dissociation rates and autoxidation [ 53 ]. Investigations of natural H 2 S donors such as garlic and synthetic donors is ongoing, but less is known about these therapies when compared to CO-releasing agents.…”
Section: Cardioprotection By Gasotransmittersmentioning
confidence: 99%
“…In its carcinogenic roles, H 2 S is involved in both the inhibition and advancement of cancer [ 5 , 8 , 9 , 10 ], while in its non-carcinogenic function, it has been found that H 2 S plays a significant role in the development of oral diseases [ 11 , 12 ], respiratory diseases [ 13 , 14 ], cardiovascular diseases [ 15 , 16 , 17 ], and common kidney diseases [ 18 , 19 , 20 ]. Consequently, these molecules have a tremendous impact on, and regulate the function of the mammalian system [ 1 , 21 ].…”
Section: Introductionmentioning
confidence: 99%